Effects of Abiotic Factors on the Geographic Distribution of Body Size Variation and Chromosomal Polymorphisms in Two Neotropical Grasshopper Species (Dichroplus: Melanoplinae: Acrididae) - Claudio J. Bidau; Carolina I. Miño; Elio R. Castillo; Dardo A. Martí (Psyche: A Journal of Entomology)
We review the effects of abiotic factors on body size in two grasshopper species with large geographical distributions: Dichroplus pratensis and D. vittatus, inhabiting Argentina in diverse natural habitats. Geographical spans for both species provide an opportunity to study the effects of changes in abiotic factors on body size. The analyses of body size distribution in both species revealed a converse Bergmannian pattern: body size is positively correlated with latitude, altitude, and seasonality that influences time available for development and growth. Allen’s rule is also inverted. Morphological variability increases towards the ends of the Bergmannian clines and, in D. pratensis, is related with a central-marginal distribution of chromosomal variants that influence recombination. The converse Bergmannian patterns influence sexual size dimorphism in both species but in different fashions. Body size variation at a microspatial scale in D. pratensis is extremely sensitive to microclimatic clines. We finally compare our results with those for other Orthopteran species.